Protective Role for Tissue Inhibitor of Metalloproteinase-4, a Novel Peroxisome Proliferator–Activated Receptor-γ Target Gene, in Smooth Muscle in Deoxycorticosterone Acetate–Salt Hypertension. Issue 1 (January 2016) - Ketsawatsomkron, Pimonrat; Keen, Henry L.; Davis, Deborah R.; Lu, Ko-Ting; Stump, Madeliene; De Silva, T. Michael; Hilzendeger, Aline M.; Grobe, Justin L.; Faraci, Frank M.; Sigmund, Curt D.
Abstract : Loss of peroxisome proliferator–activated receptor-γ (PPARγ) function causes hypertension, whereas its activation lowers blood pressure. Evidence suggests that these effects may be attributable to PPARγ activity in the vasculature. However, the specific transcriptional targets of PPARγ in vessels remain largely unidentified. In this study, we examined the role of smooth muscle PPARγ during salt-sensitive hypertension and investigated its transcriptional targets and functional effect. Transgenic mice expressing dominant-negative PPARγ (S-P467L) in smooth muscle cells were more prone to deoxycorticosterone acetate–salt–induced hypertension and mesenteric arterial dysfunction compared with nontransgenic controls. Despite similar morphometry at baseline, vascular remodeling in conduit and small arteries was enhanced in S-P467L after deoxycorticosterone acetate–salt treatment. Gene expression profiling in aorta and mesenteric arteries revealed significantly decreased expression of tissue inhibitor of metalloproteinase-4 (TIMP-4) in S-P467L. Expression of TIMP-4 was increased by deoxycorticosterone acetate–salt treatment, but this increase was ablated in S-P467L. Interference with PPARγ activity either by treatment with a PPARγ inhibitor, GW9662, or by expressing P467L PPARγ markedly suppressed TIMP-4 in primary smooth muscle cells. PPARγ binds to a PPAR response element (PPRE) in chromatin close to the TIMP-4 gene in smooth muscle cells, suggesting that TIMP-4 is a novel target of PPARγ. The interference with PPARγ and decrease in TIMP-4 were accompanied by an increase in total matrix metalloproteinase activity. PPARγ-mediated loss of TIMP-4 increased, whereas overexpression of TIMP-4 decreased smooth muscle cell migration in a scratch assay. Our findings highlight a protective mechanism induced by PPARγ in deoxycorticosterone acetate–salt treatment, establishing a novel mechanistic link between PPARγ and TIMP-4. Abstract : Supplemental Digital Content is available in the text.